The impact of defamilisation measures on gender and pensions: a comparison between the UK and seven other European countries. (11th October 2017) - Foster, Liam; Chau, Ruby; Yu, Sam
Abstract : This article uses individual-based and state-led care-focused defamilisation indices to explore women's employment opportunities and experiences and their implications for pension contributions. These two types of defamilisation indices are applied to eight European countries (Belgium, Finland, France, the Netherlands, Denmark, Norway, Sweden and the UK) which shows that the UK has less generous defamilisation measures than its European counterparts. It indicates that the use of defamilisation measures along with pension policies which are not based on the male breadwinner ideology have the capacity to moderate economic inequalities between men and women in older age.